SPATIAL DISTRIBUTION OF THE EARTHQUAKE EPISENTRUM BASED ON GEOGRAPHIC INFORMATION SYSTEM (GIS) ON AMBON ISLAND - Mohammad Amin Lasaiba; Hajirun Arfa (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2022)
An earthquake is shaking on the earth's surface resulting from seismic waves due to the sudden release of energy from within the earth. This study examines the spatial distribution of the earthquake hypocenter based on the Geographic Information System on Ambon Island. The research method used is descriptive qualitative and spatial which emphasizes spatial pattern, spatial structure, and spatial tendency. Data were obtained from geological maps, topographic maps, land use maps, Digital Elevation Model (DEM) SRTM 30 m resolution, as well as secondary data in the form of earthquake epicenter data from BMKG, as well as literature related to the problems studied. This data is then processed using ArcGis v software. 10.6 Ermapper 7.2 and Global Mapper v. 23.1. The results of the research show that the September 26, 2019, Ambon earthquake, whose location is concentrated between the islands of Ambon and Haruku, extends north to the southwest of Kairatu, Seram Island. The location of the epicenter is a tectonic active area. The area of Seram Island and its surroundings is close to the Seram fault which can generate a large earthquake with a thrust type of fault. Earthquakes with a magnitude of 3.0 SR to 4.0 SR are very common on Ambon Island, while earthquakes of 5.0 SR and above are rare and almost all of these earthquakes fall into the category of shallow earthquakes (< 70 km), namely with an average depth of 10 Km.